Repair of Morgagni Hernias with Large Defect in Adult Using Prolene Mesh: A Case Report - Desianto, Radian Dwi; Hayuningrat, Prima Kharisma (Surgical Residency Program Syiah Kuala University, 2025)
Introduction: A diaphragmatic hernia is a rare condition. A Morgagni hernia is one of four type of diaphragmatic hernia and it’s located in anterior and retrosternal location. This condition can be caused by trauma or congenital condition. The defect of Morgagni originally is small. Incidental ﬁnding during X-ray examinations performed for symptoms not related to the hernia or when symptoms develop as a result of incarceration, strangulation and visceral rupture inside the chest cavity. Case Report: In this case, we present a 35-year-old man with a 5-year history of stomach discomfort and episodes of severe dyspnea who arrived to the emergency room, during his medical work-up we incidentally found an intrathoracic gastric bubble. A laparoscopy surgery was performed but the operator did not find any holes. We decided to perform thoracotomy; the findings were in the form of intestinal entry into the thoracic cavity without any sign of incarcerated or necrotic tissue. Then, a laparotomy was performed by digestive surgeon to returns the intestine to abdominal cavity. Thoracic surgeon was involved to close the defect, which is a large defect, for that reason we choose to use prolene mesh. Discussion: This pathology is infrequent in adults, among this age group, there are two different clinical presentations: asymptomatic patients who are diagnosed incidentally when abdominal organs are found in the thorax in a chest CT scan, and symptomatic patients due to side effects of incarceration, strangulation, hemorrhage and visceral perforation in the chest cavity. Morgagni’s defect was found to be large so it was decided to use a mesh. Conclusion: Diaphragmatic hernias are rare among adult population, and they are usually asymptomatic, in this case we presented a symptomatic patient, diagnosed with a chest radiograph and treated surgically. The surgical approach for the resolution of this pathology is variable and it depends on the presence and severity of visceral complications. This patient, who has wide Morgagni's hernia was treat by mesh to close the defect